Deskripsi Pemanfaatan Media pada Mata Pelajaran IPAS Kelas V di SDN 14 Pontianak Selatan - Iman, Darul; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda; Elyasmad, Elyasmad (YASIN, 2025)
This research aims to describe the use of learning media in Class V science and science subjects at SDN 14 South Pontianak. The research method used is qualitative research with a descriptive research method approach. This research data collection technique uses observation, interviews and documentation. The participants in this research were the principal, class V teacher, and class V students. Data analysis was inductive/qualitative in nature, the research results showed that during the drawing process data was produced by describing the state of availability and use of class V learning media as seen at SDN 14 South Pontianak as it is, non-projection based learning media, such as pictures, diagrams and simple teaching aids are often used by teachers to support the teaching and learning process. Using this media not only helps students understand the material more easily, but also increases interest and motivation to learn. However, the limited media available is one of the obstacles in implementing learning. This research recommends increasing the availability of learning media as well as training for teachers to utilize technology as an alternative in the learning process. And also teachers play an important role in the successful use of learning media.